Self-Efficacy and the Competency of Nursing Students Toward the Implementation of Evidence-Based Practice - Yusshy Kurnia Herliani; Hasniatisari Harun; Anita Setyawati; Kusman Ibrahim (Jurnal Ners, 2018)
Introduction: Professional nurses should have adequate competency in order to apply Evidence Based Practice (EBP) in their nursing care. However, many nurses provide nursing care based on traditions, habits and personal experience. Less confidence in the feeling of nurses about their competency when employing EBP could inhibit successful EBP implementation in nursing care. Therefore, introducing and applying EBP during clinical placements in the Ners program is essential to form a professional attitude and to provide a basic level of experience when applying EBP in patient care. However, the self-efficacy and competence of the students when applying EBP has not yet been evaluated properly and there is little known about the nursing students’ competences and self-efficacy toward EBP implementation during clinical practice. Thus, the study aims to describe the self-efficacy and competency of nursing students toward the implementation of EBP, while also investigating the relationship between self-efficacy and the competency of nursing students in the implementation of EBP.Methods: This descriptive correlational study involved 120 nursing students who were actively registered on the Ners program 2016/2017. The data was collected by using the self-reporting Evidence-Based Practice Questionnaire (EBPQ), which was then analysed descriptively and inferentially using statistics.Results: The results of this study revealed that more than half (55%) of the participants had a high score of self-efficacy and almost half (49%) were categorised as having a high competence when implementing EBP. The self-efficacy score was significantly correlated to the score of competency (r = 0.607, p < 0.01).Conclusion: This study recommends that the development of the students’ competence in implementing EBP is essential to promote self-efficacy when applying EBP, and vice versa.